2018
DOI: 10.1186/s12943-018-0866-1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancers of follicular origin in a genomic light: in-depth overview of common and unique molecular marker candidates

Abstract: In recent years, thyroid malignances have become more prevalent, especially among women. The most common sporadic types of thyroid tumors of follicular origin include papillary, follicular and anaplastic thyroid carcinomas. Although modern diagnosis methods enable the identification of tumors of small diameter, tumor subtype differentiation, which is imperative for the correct choice of treatment, is still troublesome. This review discusses the recent advances in the field of molecular marker identification vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 139 publications
(140 reference statements)
5
37
1
3
Order By: Relevance
“…7,10,19,20 PTC samples were dominated by BRAF V600E mutations which were consistent with the previous studies showed the BRAF V600E mutation rate was 29% to 90%. 4,16,[20][21][22] Ke et al, showed the mutation types were point mutations, indel (insert and deletion) mutations and gene fusions in PTC. 20 However, only point mutations and gene fusions were detected in current study.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,19,20 PTC samples were dominated by BRAF V600E mutations which were consistent with the previous studies showed the BRAF V600E mutation rate was 29% to 90%. 4,16,[20][21][22] Ke et al, showed the mutation types were point mutations, indel (insert and deletion) mutations and gene fusions in PTC. 20 However, only point mutations and gene fusions were detected in current study.…”
Section: Discussionmentioning
confidence: 99%
“…У дітей трапляється зрідка -до 5% випадків [32]. FTC є агресивнішим за РТС типом раку ЩЗ і характеризується 95% 5-річним виживанням [33]. Для цього типу раку характерною є дерегуляція понад 400 генів.…”
Section: вступunclassified
“…Становить близько 1-5% від усіх злоякісних новоутворень ЩЗ, натомість є причиною понад 50% смертей від усіх видів раку ЩЗ. Прогноз захворювання є вкрай несприятливим [9]. Медіа на виживання становить 4 місяці (цей показник не поліпшується впродовж останніх 50 років) унаслідок неконтрольованого системного метастазування [10].…”
Section: медулярна карцинома (мтс)unclassified